IMPLEMENTASI SISTEM INFORMASI MANAJEMEN OBJEK PAJAK SISIMOP (Studi Di Kantor UPT Dispenda Provinsi Riau Kota Bagan Siapi-api Tahun 2015) - Pratama, Fery Putra; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the management of information management systems subject to tax in order to increase local tax revenue Riau Technical Implementation Unit Revenue Chart Siapi-fire Revenue Service Riau Province. The underlying doing this study is the management of information management systems subject to tax at the Technical Implementation Unit Revenue Chart Siapi-fire Revenue Service of Riau province has not done service-based e-systems such as e-SPT, e-Filing, e-Billing and e -Registration. The impact is the number of potential tax objects are not recorded, than the level of awareness and taxpayer compliance is also low.This study uses the theory of the policy with a focus on the implementation of policies for the implementation of a management information system to tax is part of the implementation of the policy of the Act No. 28 Year 2009 on Regional Taxes and Riau Provincial Regulation No. 08 Year 2011 on Regional Taxes. This study was conducted with a qualitative approach and descriptive data analysis.The results of this study indicate that the implementation of information management systems subject to tax on income UPT-fire Bagan Siapi faced with external problems that lack of trust and public awareness of the tax. In addition, the quality of human resources and management information systems to tax is still done manually is also a problem in the implementation of management information system to tax in order to increase the reception area of a sector of local taxes.Keywords: Tax, Tax Object Management Information Systems, Management, Local Taxes